DATAFICATION IN THE PUBLIC SECTOR: EXPLORING THE BORDERS BETWEEN PUBLIC SERVICES AND CITIZENS - Spilker, Hendrik Storstein; Reuter, Lisa; Broomfield, Heather; Aasback, Anne; Dahl-Jørgensen, Tangni Cinningham (AoIR Selected Papers of Internet Research, 2020)
This panel presents on-going research from a large research project on digital infrastructures and citizen participation in the Nordic countries, with a focus on the datafication of the public sector and the construction of new borders between public services and citizens. In recent years, governments have faced increasing pressures to become datafied or “data-driven”. A more data-driven public is said to be able to develop a whole new range of services that are envisaged to result in better services, more effective government, more transparency in the public sector, more just service delivery, and the empowerment of citizens. The panel critically examines the challenges that arise when the precepts are to be converted into working services – such as: What kinds of foreseen and unforeseen transformations does the development of new services give rise to? • What kinds of resistance are the new services facing? • What new forms of expertise, enrollment of new actors, organizational restructuring and redelegation of roles and relations are needed? • How are citizens/clients envisioned and inscribed into the scenarios for future public administration? • How are citizens/clients consulted in the design and development of the services? • How are the new services experienced by citizens/clients? In sum, the presentations in this panel span a range of urgent themes related to the construction of borders (and alleys) between public sector services and citizens – from anticipations to effects and efforts.